Unionization and Cost of Production: Compensation, Productivity, and Factor-Use Effects - Eberts, Randall W.; Stone, Joe A. (Journal of Labor Economics, 1991)
Unionization affects cost of production through compensation premia, technology shifts, and deviations from the least-cost combination of inputs. The first two are familiar, but the last is not. This article distinguishes the three effects, illustrates the factor-use effect, and suggests that it may resolve several apparent inconsistencies: union-induced cost effects appear larger than those implied by union compensation and productivity differentials; union compensation and productivity differentials suggest a larger effect on labor intensity of output than is observed; and employers complain that union work rules reduce productivity when there is little evidence that this is so.